Discriminant Analysis for Determination of Early Childhood Education Accreditation In Southeast Sulawesi Province - Makkulau, Makkulau; Wibawa, Gusti N.A.; Ampa, Andi Tenri; Pannangngareng Makkulau, Andi Tenri; Harini, Sri; Mulyanto, Angga Dwi (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2023)
Discriminant Analysis is a statistical analysis that can classify cases on independent variables into groups or categories of dependent variables. The main objective of this research is classify eight indicators of the National education standards (SNP) early childhood and classify the accreditation value of early childhood (PAUD) in Southeast Sulawesi Province. The method used in this study used discriminant analysis. Accreditation value factors used in this study include Standards for Child Development Achievement Levels (X1), Content Standards (X2), Process Standards (X3), Standards for Educators and Education Personnel (X4), Facilities and Infrastructure Standards (X5), Management Standards (X6), Financing Standards (X7) and Education Assessment Standards (X8). Based on the results of data analysis, 8 SNP Indicators qualify as a form of discriminant equation model and accreditation value obtained based on the calculations of the National accreditation organization (BAN) PAUD and Non Fromal Education (PNF) Southeast Sulawesi are classified as follows: there are divided into 3 classifications, namely Accreditation C is 91.7%, Accreditation B is 85.1%, and for Accreditation A is 100%. So, the accuracy of the classification is 87.5%.